The Anti-inflammatory effectiveness of a combination of basil leaf extract (Ocimum americanum L) and turmeric rhizome (Curcuma domestica Val) in mice with carrageenan induction - kamalia dafira Dafira; Mohammad Rofiq Usman; Sholihatil Hidayati (LPPM Universitas dr. Soebandi, 2024)
Background : Inflammation is the body's response to tissue injury, usuallycaused by physical trauma, damaging chemicals or microbiological agents.Basil leaves and turmeric rhizomes have been shown to be effective as antiinflammatories. The combination of these plants aims to determine the effectivedose as an anti-inflammatory.Objective: To determine the anti-inflammatory effectiveness of a combinationof basil leaf extract (Ocimum americanum L) and turmeric rhizome (Curcumadomestica Val) in rats with carrageenan induction.Method: This study is an experimental laboratory study using 28 male white ratsof the Wistar strain induced by 1% carrageenan. KN using CMC Na, KP sodiumdiclofenac, EK dose of 10 mg/KgBW, RK extract dose of 600 mg/KgBW andEKRK dose composition (2.5: 450 mg/KgBW, 5: 300 mg/KgBW, and 7.5: 150mg/KgB B ) . Continued with anti-inflammatory power. then data analysis usingSPSS version 26 began with a normality test and a homogeneity test as arequirement for the one-way ANOVA test.Results: The percentage results of anti-inflammatory power of KP 28.71%, EK10 mg/KgBB 33.00%, RK 600 mg/KgBB 33.23%, and EKRK 2.5: 450 mg/KgBB,5: 300 mg/KgBB, dose 7.5: 150 mg/KgBB respectively, namely 31.21%,28.65%, and 28.35% . The data obtained were continued with statistical testsusing SPSS version 26. The results of statistical tests using normality andhomogeneity tests were P> 0.05 and the one-way ANOVA test value was P>0.05.Conclusion: It can be concluded that the results of this study showed that in alltreatment groups it was proven effective as an anti-inflammatory. So it is hopedthat this study can be used as a reference for further research.